Pengaruh Motivasi, Biaya Pendidikan, Dan Lama Pendidikan Terhadap Minat Mahasiswa Akuntansi Untuk Mengikuti Pendidikan Profesi Akuntansi (PPAk) (Studi Kasus Pada Mahasiswa Akuntansi di Universitas Muhammadiyah Surakarta) - Setyaningsih, Pita; , Dr. Noer Sasongko, SE, M.Si, Ak (2016)
This study was conducted to examine the effect of motivation, the cost of education, and education on the old accounting student interest to follow the accounting profession education (PPAk) at the Faculty of Economics and Business (FEB) Muhammadiyah University of Surakarta (UMS). The study population was FEB accounting students Muhammadiyah University of Surakarta. This study took a sample of accounting students in 2013 who is still an active force following the lecture by using a convenience sampling method. The primary data source using the method of data collection in the form of questionnaires used in this study. There are 81 questionnaires which can be treated using multiple linear regression analysis of data using SPSS 17.0. Based on the results of the analysis conducted in this study, we can conclude that the motivation career, the motivation to seek knowledge, motivation degree, the cost of education, and the length of education affect the interest of accounting students to participate in education accounting profession (PPAk), while the economic motivation and motivation to follow Wipe does not affect the interest of the education of accounting students to follow the accounting profession (PPAk) for accounting students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta.